2016
DOI: 10.1016/j.neuropharm.2015.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of kynurenine aminotransferase II reduces activity of midbrain dopamine neurons

Abstract: Kynurenic acid (KYNA), a neuroactive metabolite of tryptophan, is elevated in the brain of patients with psychotic disorders. Therefore, lowering brain KYNA levels might be a novel approach in the treatment of psychotic disorders. The present in vivo electrophysiological study aimed to investigate the effect of an inhibitor of kynurenine aminotransferase (KAT) II, the primary enzyme for KYNA synthesis, on dopamine (DA) neurons in the ventral tegmental area (VTA). Acute administration of the KAT II inhibitor PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 50 publications
0
28
0
1
Order By: Relevance
“…Decreased concentration of KYNA may be important not only for cognition but also for psychosis because increased KYNA concentration may be associated with psychosis [103-105]. Furthermore, inhibition of kynurenine aminotransferase II was associated with a marked reduction in dopamine firing activity in the ventral tegmental area [106]. KP modulations may be potential targets of novel antipsychotics [107].…”
Section: Kynurenine Pathwaymentioning
confidence: 99%
“…Decreased concentration of KYNA may be important not only for cognition but also for psychosis because increased KYNA concentration may be associated with psychosis [103-105]. Furthermore, inhibition of kynurenine aminotransferase II was associated with a marked reduction in dopamine firing activity in the ventral tegmental area [106]. KP modulations may be potential targets of novel antipsychotics [107].…”
Section: Kynurenine Pathwaymentioning
confidence: 99%
“…Based on previous suggestions that chronic excessive alcohol consumption leads to activation of the immune system (92) involving TLR4 (100), it is tempting to suggest that the LPS translocated from the gut following CI EtOH could produce a neuroinflammatory response, leading to the induction of IDO activity, which results in the observed increase in brain Kyn levels. Supporting this, preclinical studies showed that peripheral LPS injection produces an increase in central proinflammatory cytokines and IDO expression (101103) as well as in Kyn concentration in brain tissue (104).…”
Section: Discussionmentioning
confidence: 86%
“…The dose and route for PF‐04859989 administration were chosen based on previous publication (Linderholm et. al., ). Neurological function was evaluated at 24 hr after SBI after which brain samples were collected for western blot.…”
Section: Methodsmentioning
confidence: 97%